Peran Kepala Sekolah dalam Meningkatkan Kinerja Guru Di SMK Negeri 3 Karang Baru Kab. Aceh Tamiang - Wardiana (Journal of Technology and Literacy in Education, 2022)
The principal influences the teacher's ability to improve the quality of learning so that school goals can be achieved optimally. The leadership role of school principals in school organizations is very important because the strategic role of school principals influences teacher performance in implementing learning process activities. As an educational leader, the school principal has quite heavy duties and responsibilities. The effectiveness of the principal in implementing management functions is the accuracy of applying the ability of the principal in planning, organizing, actuating and controlling as well as the utilization of all educational resources including manpower, funds, facilities and infrastructure including information optimally, namely showing the extent to which the principal carry out its main tasks properly and correctly to achieve goals. The purpose of this literature study aims to identify, explain and analyze the role of school principals in improving teacher performance. The results of the principal's work program provide a positive climate for teachers and staff at SMK Negeri 3 Karang Baru. The teacher performance supervision program is also applied properly so as to produce the quality of relationships and maximum performance in the teaching and learning process. Teachers are also active in providing ideas and input for school principals, adding to learning knowledge in class and applying it in learning. Obstacles to improving the quality of education are the incomplete facilities and infrastructure in schools and environmental factors. The solution to improving the quality of education is collaboration and submission of proposals for additional facilities and infrastructure to the relevant education office.